The Breakdown of Credit Relations Under Conditions of a Banking Crisis : A Switching Regime Approach - Munoz, Sonia (Washington, D.C. : International Monetary Fund, 2000)
This paper empirically analyzes the effects of a banking crisis on bank credit to the private sector for a panel of developing, developed, and transition economies for the period 1970-1998. The model illustrates how the behavior of the bank credit function changes during a banking crisis, reflecting a generalized disruption in the stability of behavioral parameters. Usual links such as interest rate signaling for lending, and synergy between deposits and loans, fall apart. Moreover, this study gives support to Third Generation Models in their ability to predict banking crises. Based on the empirical findings, the paper then provides policy implications for monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet